2008
DOI: 10.1111/j.1751-553x.2007.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

The biological characteristics of dendritic cells derived in vitro from myelogeneous leukemia cells and healthy donor cells

Abstract: Successful adoptive immunotherapy for leukemia depends on the generation of T cells that can specifically react with malignant cells. Dendritic cells (DCs) are important antigen-presenting cells in the development of antileukemia T-cell responses. Mononuclear cells (MNC) were isolated from peripheral blood or bone marrow of patients with chronic myelogenous leukemia (CML), and acute myelogenous leukemia (AML). After incubation with granulocyte-macrophage colony-stimulating factor, interleukin (IL)-4, and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Our findings are consistent with some previous studies which reported that only in about 50-70% of AML patients could blasts be successfully differentiated into dendritic cells [25][26][27]39]. In optimal combination condition, the median recovery percentage of leukemic DC generation based on phenotypic criteria was 42% (range, 28-50%).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our findings are consistent with some previous studies which reported that only in about 50-70% of AML patients could blasts be successfully differentiated into dendritic cells [25][26][27]39]. In optimal combination condition, the median recovery percentage of leukemic DC generation based on phenotypic criteria was 42% (range, 28-50%).…”
Section: Discussionsupporting
confidence: 95%
“…The most important advantage of generating AML-DC is the fact that all of the assumed leukemia-specific antigens would be presented by appropriate MHC molecules [38]. Recently, cocktails containing synthetic TLR agonists emerged as an attractive alternative for the induction of DC maturation [17][18][19]39]. Thus, we tried to optimize the generation and TLR agonist-dependent maturation of DCs derived from blasts of newly diagnosed AML patients.…”
Section: Discussionmentioning
confidence: 98%
“…DCs were cultured according to previous report[21-24]. Peripheral blood mononuclear cells (PBMCs) were obtained from healthy volunteers and suspended in 5-mL culture flasks with RPMI 1640 containing 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the PKC-induced differentiation associated with the down-regulation of BCR-ABL activity, which raises the possibility that CML-derived DC vaccines will be less effective in presenting leukemia-specific Ags [44]. The DC abnormalities in patients with CML may be abrogated by the proper in vitro stimulation of leukemic DCs [45-47]. However, in 2006, a phase I immunotherapy CML trial demonstrated that DC injections were well tolerated and safe, while no clinical responses was found [48].…”
Section: Vaccinesmentioning
confidence: 99%